Mad Max : Fury Road : inspired artists - Miller, George, 1945 March 3- (Burbank, CA : Vertigo, DC Comics, 2015)
Collects artwork inspired by the world of Mad Max from sixty-five artists, including John van Fleet, Jim Lee, and Rebekah Isaacs.
"Based upon the screenplay written by George Miller, Brendan McCarthy, and Nico Lathouris."
Keywords: Mad Max: fury road (Motion picture); Motion pictures in art; Motion pictures and comic books; Apocalyptic art; Art -- 21st century